Bringing socially-critical pedagogies to life through stories. Issue 3 (2nd September 2021) - Scorringe, Aaron; Philpot, Rod; Bruce, Toni
ABSTRACT : New Zealand and Australia introduced health and physical education curricula espousing a socially-critical perspective more than two decades ago. Yet, despite growth in advocacy and teaching resources, there is little research exploring how HPE teachers are enacting these pedagogies. This article addresses the challenge of understanding what six HPE teachers 'do' in the name of being socially critical through two ethnographic fiction stories that bring their experiences to life. The results show that HPE teachers use socially-critical pedagogies in three main ways that resonate with Paulo Freire's pedagogical concepts. First, they enter into dialogue with students to develop critical consciousness. Second, through problem-posing techniques, they challenge students to question their own attitudes, values and assumptions. Third, they understand the importance of using socially-critical pedagogies to raise consciousness and to lead students into taking action to bring about more equitable outcomes in relation to social justice.